Study guides

☆☆

Q: What is b squared plus ab minus two minus two b squared plus two ab?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Let y= ab+(- a)(b) +(-a)(-b) factor out -a y= ab+(-a){b+(-b)} y=ab+(-a)(0) y =ab -------------------(1) now factor out b y= b{a+(-a)}+(-a)(-b) y= b(0) +(-a)(-b) y= (-a)(-b)-----------------(2) equate (1) and (2) (-a)(-b)=ab minus x minus = positive

The length of its side squared.

The square root of 149 (7 squared plus 10 squared equals 149).

If, as is normal, ab represents a times b, etc then ab + ab + cc = 2ab + c2 which is generally not the same as abc.

For two vectors A and B, the scalar product is A.B= -ABcos(AB), the minus sign indicates the vectors are in the same direction when angle (AB)=0; the vector product is ABsin(AB). Vectors have the rule: i^2= j^2=k^2 = ijk= -1.

Related questions

(b-c)(a+b)-ac

6(ab - ac + b2 - bc)

(a + x^2)(b + y^2)

(a+b)(a squared-ab+b squared)

x2y + axy + abx + a2b Factor by grouping. xy(x + a) + ab(x + a) (xy + ab)(x + a)

C minus B equals AB

No. The child could be either AA or Ao and they would have plus or minus, depending on if the a plus parent has plus plus, or plus minus

That factors to (a + 1)(a + b) a = -1, -b b = -a

Let y= ab+(- a)(b) +(-a)(-b) factor out -a y= ab+(-a){b+(-b)} y=ab+(-a)(0) y =ab -------------------(1) now factor out b y= b{a+(-a)}+(-a)(-b) y= b(0) +(-a)(-b) y= (-a)(-b)-----------------(2) equate (1) and (2) (-a)(-b)=ab minus x minus = positive

This expression can be factored. ab + 3a + b2 + 3b = a(b + 3) + b(b + 3) = (a + b)(b + 3)

No, AB+ people can receive blood from all blood groups.

4

People also asked